The 2014 Popular Education Network Conference (Concept: The Journal of Contemporary Community Education Practice Theory, 2014)
The sixth International Conference of the Popular Education Network (PEN) was held from April 24-26, 2014. Hosted by the University of Malta, Valletta Campus, this conference built on the success of previous PEN conferences held in Edinburgh (2000), Barcelona (2002), Braga (2004), Maynooth (2007) and Seville (2011). The network brings together academics in higher education with an interest in supporting popular education in communities. Established in 1997, the Popular Education Network was originally intended to politicise the theory and theorise the practice of popular education in a very particular and uncompromising way. As such, in this network, popular education is understood to be popular, as distinct from merely populist, in the sense that it is• Rooted in the real interests and struggles of ordinary people,• Overtly political and critical of the status quo, and• Committed to progressive social and political change. (see Crowther, J., Martin, I. and Shaw, M. (1999) (eds) Popular Education and Social Movements in Scotland Today, Leicester: NIACE)